Development of Visual Basic Application PPT Media Based on Cooperative Model Type of NHT to Increase Motivation and Mastery of Physics Concepts - Maryana, Lisa; Hikmawati, Hikmawati; Rokhmat, Joni; Susilawati, Susilawati (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
This development research aims to create a product in the form of Power Point Visual Basic Application (PPT VBA) media based on the Numbered Heads Together (NHT) cooperative model on valid, practical, and effective business and energy materials, so that it can be used to measure motivation and mastery of concepts. students at school. The type of research used is research and development (Research & Development) with the ADDIE model, namely analysis, design, development, implementation, and evaluation. Data collection techniques were obtained from the results of filling out the validation sheet by 6 validators, namely 3 expert validators and 3 practitioner validators using a Likert scale. Practicality is obtained from the results of student response questionnaires. Effectiveness was obtained from a learning motivation questionnaire and a concept mastery test. Validity is obtained from the results of the validity assessment by expert validators and practitioners, namely 84% and 89%, respectively, with very valid categories. Practicality is obtained from the results of the student response questionnaire with an average value of 99.45% in the very practical category and gets a positive response. The effectiveness is obtained from the results of the motivation questionnaire after learning with an average value of 71.09% in the high category and the results of the concept mastery test calculated using N-Gain getting an average value of 0.59 in the medium category. So that it can be concluded, the development of PPT Visual Basic Application media based on the cooperative model of the NHT type is valid, practical, and effective to increase learning motivation and mastery of students' concepts on business and energy materials in school learning